Rancang Bangun Sistem Informasi Persediaan Barang Masuk Dan Barang Keluar Berbasis Web Pada CV. Ekonomi Teknologi Abadi (ETA) Mining - Ando Noel Simorangkir; Dian Gustina (Jurnal Ilmiah Teknik Informatika (TEKINFO), 2026)
The development of digital technology and the growing public interest in cryptoassets, particularly Bitcoin, have led to a growing need for supporting equipment such asmining rigs and related components. CV. Ekonomi Teknologi Abadi (ETA) Mining, amining equipment provider, faces challenges in managing inventory, which is still donemanually using records and spreadsheets. This method creates various obstacles, suchas inconsistencies in stock data, delaysin stock availability information, and difficulties inpreparing inventory reports. These problems have the potential to cause financial lossesgiven the relatively high value of the goods.The system development method used is theWeb Development Life Cycle (WDLC), which includes planning, analysis, design anddevelopment, testing, implementation, and maintenance. The results of this researchareaweb-basedinventoryinformationsystem capableofmanagingstock data,incomingandoutgoinggoodstransactions, andgeneratingdaily,monthly, andannualinventoryreports. Thedeveloped system is expected to improve work efficiency, minimize recording errors, andsupport more accurate decision-making at the Abadi Technology Economy (ETA) MiningStore.